Use of femoral shaft fracture classification for predicting the risk of associated injuries. - Nikolaou, Vassilios S; Stengel, Dirk; Konings, Peter; Kontakis, George; Petridis, Gerasimos; Petrakakis, Giannos; Giannoudis, Peter V (J Orthop Trauma, 2011)
OBJECTIVES: To investigate the hypothesis that specific fracture patterns in patients with femoral shaft fractures can predict the likelihood of associated injuries. DESIGN: Retrospective cohort study. SETTING: Level I trauma center. PATIENTS/PARTICIPANTS: Consecutive patients treated because of a traumatic diaphyseal femoral fracture. MAIN OUTCOME MEASUREMENT: We studied the association between the Orthopaedic Trauma Association (OTA) fracture classification (derived from initial radiographs) and concomitant injuries of the head, spine, chest, abdomen, and pelvis with a severity of two or more points according to the Abbreviated Injury Scale by logistic regression analysis. RESULTS: One hundred forty-three of 203 patients (80 men, 63 women; mean age 54 ± 26 years) met the inclusion criteria. All patients had unilateral diaphyseal fractures, 64 OTA 32.A (45%), 46 OTA 32.B (32%), and 33 OTA 32.C (23%). In addition, 134 associated injuries were identified in 52 patients. Increasing fracture severity, as expressed by the OTA classification (ie, A, B, C), was significantly associated with a higher likelihood of thoracic (odds ratio [OR], 5.89; 95% confidence interval [CI], 2.59-13.40), pelvic (OR, 4.55; 95% CI, 2.01-10.28), upper (OR, 2.38; 95% CI, 1.27-4.48), and lower extremity injuries (OR, 3.12; 95% CI, 1.78-5.46). Fracture severity explained between 70% and 86% of the probability of having accompanying injuries. CONCLUSION: Radiographic grading of the severity of a femoral shaft fracture may signal the presence of accompanying injuries and should contribute to the clinical decision-making process in severe trauma.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cohort Studies; Female; Femoral Fractures; Humans; Male; Middle Aged; Multiple Trauma; Predictive Value of Tests; Radiography; Retrospective Studies; Risk Factors; Trauma Centers; Young Adult